Sleepiness and fatigue during driving: relationship with road traffic accidents in Peruvians highways - de Castro Mujica, Jorge Rey (2009)
A tired driver, or a driver who falls asleep at the wheel cannot perform evasion maneuvers for avoiding a car crash, or he/she may also get out of the road so easily; and the consequence of these accidents is a huge number of victims and infrastructure destruction. The information based on local studies indicates that many road accidents in Peru are caused by drivers falling asleep or because of driving so tired. We discuss in this paper the original data published in Peru and we propose some guidelines in order to address this problem.